Changes of Physicochemical Properties and Immunomodulatory Activity of Polysaccharides During Processing of Polygonum multiflorum Thunb - Gu, Donglin; Wang, Ying; Jin, Hongyu; Kang, Shuai; Liu, Yue; Zan, Ke; Fan, Jing; Wei, Feng; Ma, Shuangcheng (Frontiers in Pharmacology, 2022)
The roots of Polygonum multiflorum Thunb. (PM) have a long history of usage in traditional Chinese medicine and are still widely utilized today. PM in raw or processed form has different biological activities and is commonly used to treat different diseases. Polysaccharides are the main component of PM, and it is unclear whether their physicochemical properties and activities change after processing. In this study, the polysaccharides from 31 raw PM (RPMPs) and 9 processed PM (PPMPs) were extracted, and the physicochemical properties and immunomodulatory activity in vitro of polysaccharide samples were evaluated. Results showed that RPMPs and PPMPs had significant differences in physicochemical properties. RPMPs and PPMPs were both composed of mannose, rhamnose, glucuronic acid, galacturonic acid, glucose, galactose, and arabinose. However, RPMPs and PPMPs had significant differences in their yields, molecular weight (Mw), and the molar ratio of Glc/GalA (P < 0.05), which can be used to distinguish raw and processed PM. The fingerprint of monosaccharide composition was analyzed by chemometrics, and it was further demonstrated that Glc and GalA could be used as differential markers. The immunomodulatory activity assays indicated that RPMPs and PPMPs could significantly enhance phagocytosis and mRNA expression of cytokines in RAW 264.7 cells. In addition, the immunomodulatory activity of PPMPs with lower Mw was significantly better than that of RPMPs. This study furthers the understanding of the polysaccharides from raw and processed PM and provides a reference for improving the quality standard of PM.